Significance of SMEs in the Czech Economy and Supporting SMEs as an Instrument of the Regional Development - V. Beran; J. Frková (Acta Polytechnica, 2003)
SMEs (Small and Medium Enterprises) are important segments of the economic landscape of the Czech Republic, since half of economic production is attributable to SMEs (52.85 %). The role of SMEs in the Czech Republic is the outcome of a long history of economic development and industrialization throughout the 20th century. Large enterprises prefer to locate their factories according to range of regional opportunities. Small enterprises are more dependent on business conditions in their region. The transaction costs are relatively high for small firms. These contraints mean that regions without an attractive environment for business need to create acceptable conditions for small businesses, if they are looking for sustainable development.